Breaking the rules : a volatile season with sport's most colorful team : Charles Barkley's Phoenix Suns - Tulumello, Mike.; Cruz, Dave (Atlanta, GA : Longstreet Press, 1996)
Inside look at the Phoenix Suns discussing the personal clashes between players, changing of coaches during the season and the controversial trade of Charles Barkley after the team's dissapointing playoff performance.
Adult
Keywords: Phoenix Suns (Basketball team); Phoenix Suns (Basketball team); Basketball; Basketball